2020
DOI: 10.1590/0102-311x00059220
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural pressure: a model of body dissatisfaction for young women

Abstract: The aim of the study was to verify the influence of pressure from sociocultural agents on dissatisfaction with face and body in young women mediated by the internalization of the lean and muscular body and to identify the contribution of individual characteristics to this model. A total of 612 university female students participated of study. The students completed the Portuguese versions of the Sociocultural Attitudes Towards Appearance Questionnaire-4 and of the Body Area Scale-Revised and a sociodemographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…The portion of underweight respondents in this study sample was 20%, confirming that the belief in thinness or slimmest is the ideal appearance. Body dissatisfaction might be experienced by these students as a previous study found that females who internalised thin-low body fat were more dissatisfied with their general physical appearance (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…The portion of underweight respondents in this study sample was 20%, confirming that the belief in thinness or slimmest is the ideal appearance. Body dissatisfaction might be experienced by these students as a previous study found that females who internalised thin-low body fat were more dissatisfied with their general physical appearance (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…Body dissatisfaction can be defined as a negative attitude towards physical appearance resulting from the discrepancy between one's body perceptions and the perceived ideal body (Heider et al, 2018). It is noteworthy that many people experience body image dissatisfaction, and its rates are high, especially among women, adolescents and young adults (da Silva et al, 2020). According to Van den Berg et al (2002), it is useful to view satisfaction as a continuum, ranging from no body image satisfaction to extreme body image satisfaction.…”
Section: Body Satisfaction and Dissatisfactionmentioning
confidence: 99%
“…For decades, a thin body pattern was considered ideal for women and a muscular one for men. Currently, both sexes aim for a body type with low fat and well-defined musculature (da Silva et al, 2020). A noticeable difference between men and women is the following: contrary to findings for women, men's body dissatisfaction is a two-tailed phenomenon involving both ends of a weight continuum and men who are either above or below the acceptable range in their Body Mass Index scores, tend to be especially dissatisfied with their physical appearance (Muth & Cash, 1997).…”
Section: Body Satisfaction and Dissatisfactionmentioning
confidence: 99%
“…Las creencias y actitudes hacia el propio cuerpo son influenciadas por tendencias e ideales de belleza, representado en cuerpos delgados y musculatura bien definida para ambos géneros. Estos ideales de perfección corporal son valorados especialmente en familias, amigos y medios de comunicación, así como las redes sociales, siendo interiorizados en mayor medida por adolescentes mujeres, particularmente aquellas que presentan sobrepeso u obesidad [4][5][6][7] . En la sociedad occidental, la apariencia física es fundamental para el valor y los roles otorgados a las mujeres, el cuerpo femenino delgado se equipará con la belleza y la virtud, representando de esta manera el camino del éxito y satisfacción con la vida 8 .…”
Section: Introductionunclassified